Endoscopic postdilatation application of Mitomycin C in children with resistant esophageal strictures - Yasser K. Rashed; Mohamed El-Guindi (Korean Pediatric Society, 2019)
Background The esophagus is the most common part of gastrointestinal (GI) tract at the risk of stricture. Benign disorders are the leading causes of narrowing. Caustic ingestion is the most common cause of esophageal stricture in children, especially in developing countries. Clinical responses to the topical application of Mitomycin C in various medical procedures have been reported. Purpose The study aimed to evaluate the methodology, efficacy, and side effects of Mitomycin C in the treatment of esophageal strictures. Methods This study included 30 children with resistant esophageal strictures. Upper GI endoscopy was performed up to the area of stricture, esophageal dilatation was done, endoscopy was repeated, and Mitomycin C was applied topically under direct endoscopic vision. The effect of the procedure was followed over a period of 3-5 years. Results The response to Mitomycin C was excellent (clinically and endoscopically) in 28 patients (93.3%) and good (endoscopically only) in 2 patients (6.7%). No side effects of topical Mitomycin C in children with esophageal strictures were reported in this study. Conclusion Esophageal dilatation followed by local Mitomycin C application may be a useful strategy for treating resistant esophageal strictures.